2022
DOI: 10.1007/s10661-022-10216-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological impacts of industrial effluents on irrigation water quality, animal health and the role of calcium alginate in effluents treatment

Abstract: The effluents discharged from Mansoura Company for Resins and Chemicals Industry were evaluated for drinking and irrigation purposes. Calcium-alginate beads were used for effluents treatment in this study. Young male rats were also allowed to drink effluents at different concentrations (10%, 50%, 100%) and treated 100% effluents with calcium-alginate for 11 weeks. Results indicated high concentrations of some physicochemical parameters and Cd, Co, Fe, Mn, Ni, Pb, and Zn in effluents that exceeded the permissib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Despite the fact that the present study also positively relates to a research finding in which different bacterial isolates obtained from the soil are aggregated by means of industrial wastewater (secondary source of aggregation), the results showed adsorption of Cd and Ni at different concentrations of single-and bi-metal systems and indicated that these heavy metals not only affect the soil flora but also affect the agricultural system [57]. Similar to the presence of benzidine, 3,3 -dimethoxybenzidineand 3, or 3 -dimethylbenzidine were reported in the industrial wastewater from where the soil samples were collected.…”
Section: Discussionmentioning
confidence: 52%
“…Despite the fact that the present study also positively relates to a research finding in which different bacterial isolates obtained from the soil are aggregated by means of industrial wastewater (secondary source of aggregation), the results showed adsorption of Cd and Ni at different concentrations of single-and bi-metal systems and indicated that these heavy metals not only affect the soil flora but also affect the agricultural system [57]. Similar to the presence of benzidine, 3,3 -dimethoxybenzidineand 3, or 3 -dimethylbenzidine were reported in the industrial wastewater from where the soil samples were collected.…”
Section: Discussionmentioning
confidence: 52%